2011
DOI: 10.1080/03055698.2010.539669
|View full text |Cite
|
Sign up to set email alerts
|

Learning to collaborate: a study of nursing students’ experience of inter‐professional education at one UK university

Abstract: Educational Studies 0305-5698 (print)/1465-3400 (online) Original Article 2010 Taylor & Francis 00 0 0000002010 PaulStepney P.M.Stepney@wlv.ac.ukCollaborative working has been part of official government policy for some time and whilst a great deal has been claimed about its benefits, in terms of better quality services and improved outcomes, it would seem that translating policy intentions into practice has hitherto proved a challenge. Moreover, evidence concerning the effectiveness of collaborative working i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…In one study perception of team efficacy decreased after graduation.3 papers [20, 49, 50];- Exposure to IP teams - Students ask for longitudinal integrated IPE and longitudinal clerkships- IPE as a training in comparison with lectures resulted in significantly higher mean scores on the subscales ‘quality of care’ and ‘patient-centered care’.7 papers[33, 35, 3941, 57, 71]- Stimulating teamwork training - Training of team communication skills enhances motivation and positive attitudes toward IPC. Students had learned about their performance and lack of professional skills alongside team skills.6 papers[17, 18, 25, 4244]- Teacher facilitating reflection - A teacher helping students think, plan, do and check their work, thus stimulating teamwork rather than teaching knowledge.6 papers[23, 24, 4649, 76]- Shared learning - Value in learning about professional differences and identity. Students saw the benefits of shared learning, medical students saw the advantages only early in their training.18 papers[21, 22, 34, 35, 37, 39, 43, 44, 5459, 68, 74, 75, 77]- Learning in authentic context - Clinical realism, like simulation or interprofessional training unit, offered students an opportunity to identify other professionals’ functions in relation to patient care and to clearly assess and describe patients’ problems and needs.1 paper [49]- Readiness for IPE and attitude towards health care teams improved after IPE involving teaching through practice and decreased after IPE involving teaching only through lectures.2 papers [43, 77]- Integrating IPE & specific learning goals - Combination of professional specific and IPE learning goals was achieved by students in advanced years (8th semester)1 paper [59]- Follow up training - A Team communication training was followed by regular IP team meetings.Barriers8 papers[17, …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In one study perception of team efficacy decreased after graduation.3 papers [20, 49, 50];- Exposure to IP teams - Students ask for longitudinal integrated IPE and longitudinal clerkships- IPE as a training in comparison with lectures resulted in significantly higher mean scores on the subscales ‘quality of care’ and ‘patient-centered care’.7 papers[33, 35, 3941, 57, 71]- Stimulating teamwork training - Training of team communication skills enhances motivation and positive attitudes toward IPC. Students had learned about their performance and lack of professional skills alongside team skills.6 papers[17, 18, 25, 4244]- Teacher facilitating reflection - A teacher helping students think, plan, do and check their work, thus stimulating teamwork rather than teaching knowledge.6 papers[23, 24, 4649, 76]- Shared learning - Value in learning about professional differences and identity. Students saw the benefits of shared learning, medical students saw the advantages only early in their training.18 papers[21, 22, 34, 35, 37, 39, 43, 44, 5459, 68, 74, 75, 77]- Learning in authentic context - Clinical realism, like simulation or interprofessional training unit, offered students an opportunity to identify other professionals’ functions in relation to patient care and to clearly assess and describe patients’ problems and needs.1 paper [49]- Readiness for IPE and attitude towards health care teams improved after IPE involving teaching through practice and decreased after IPE involving teaching only through lectures.2 papers [43, 77]- Integrating IPE & specific learning goals - Combination of professional specific and IPE learning goals was achieved by students in advanced years (8th semester)1 paper [59]- Follow up training - A Team communication training was followed by regular IP team meetings.Barriers8 papers[17, …”
Section: Resultsmentioning
confidence: 99%
“…Where an interprofessional group had one or more facilitating health care professionals, students perceived them as helpful when they were from their own and other professions [25]. Participation of the preceptor was a facilitator of IPE [18].…”
Section: Resultsmentioning
confidence: 99%
“…Other important challenges for integrated care are the institutional context, such as the financing system and legislation [ 2 ]. Moreover, organizational culture is found to be of great importance to inter-sectorial collaboration [ 3 ] and important barriers are identified in professional tribalism, and status and power differentials [ 4 ]. In a previous report, 10 challenges were identified that must be addressed to achieve successful collaboration, including careful preparation and organization by the leaders, and supportive home management [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our learning mirrored that of our students as we successfully moved beyond our professional silos and adopted a professional mindset that allowed us to learn with, from and about each other's work. Like Stepney et al (2011) suggests for students, we too established a strong commitment to collaborative practice.…”
Section: Resultsmentioning
confidence: 99%
“…This article reports on student responses to the questionnaire using a mixed methods design (Cresswell & Clark 2011;Stepney, Callwood, Ning & Downing, 2011). Ethical approval for the research was obtained through the University of British Columbia Okanagan's Behavioural Research Ethics Board prior to the first workshop in 2009 and was renewed before the second workshop in 2010.…”
Section: Methodsmentioning
confidence: 99%